The Effect of Pressure or Non-Pressure Cooked Rice on Glucose Response and Satiety in Healthy Korean Women. (29th May 2020) - Kim, Mi-Hyun; Lee, Hyun Jung
Abstract: Objectives: This study examined the effect of pressure or non-pressure cooked rice on glycemic response and satiety of healthy women in South Korea. Methods: A total of 18 non-obese women aged 23–54 years participated in this study. On two separate mornings at intervals of 5 days or more, all participants were served with rice (200 ml) that was cooked either with pressure (using by an electronic pressure rice-cooker) or without pressure (using by in an electronic rice-cooker) and side dishes in a random order. The 200 ml of pressure cooked-rice contained 30 kcal higher in calories than the same amount of non-pressure cooked-rice, and the side dishes served with the cooked-rice were the same. Capillary blood-glucose response and satiety score were measured every 15 or 30 minutes for 2 hours (3 hours for satiety) before and after consuming the test diet. We used a paired t-test to examine the difference and a significant level was set at P  < 0.05. Results: Although mean fasting glucose levels were not different, glucose levels at 30 minutes were significantly higher after eating the non-pressure cooked-rice meal than eating pressure cooked-rice meal ( P  < 0.01). However, total glucose response was not significantly different between the two meals. Though the pressure cooked-rice contained more calories than non-pressure cooked-rice, the feeling of hunger and desire to eat after eating the meals were not significantly different. Compared to eating pressure cooked-rice, feeling of fullness was lower at 60 ( P  < 0.05) and 90 ( P  < 0.01) minutes after consuming non-pressure cooked-rice meal; however, the difference was disappeared at 120 and 180 minutes after. Conclusions: This study suggests that consuming pressure cooked-rice or non-pressure cooked-rice may affect total calorie intake. The intake of non-pressure cooked-rice may be a possible way to reduce calorie intake; however further research on the long-term effect is necessary. Funding Sources: None.